Association of Estimated Glucose Disposal Rate With Risk of Abdominal Aortic Aneurysm: Evidence From a Large-Scale Prospective Cohort Study of the UK Biobank - Yuanwei Chen; Ting Zhou; Songyuan Luo; Jizhong Wang; Fan Yang; Yingqing Feng; Lixin Fang; Jianfang Luo (Reviews in Cardiovascular Medicine)
Background: Insulin resistance has been recognized as a risk factor in the pathogenesis of various diseases. The estimated glucose disposal rate (eGDR) has been widely validated as a reliable, noninvasive, and cost-effective surrogate measure of insulin resistance. However, the relationship between eGDR and abdominal aortic aneurysm (AAA) has not yet been fully elucidated. This study sought to investigate the association between the eGDR levels and the risk of AAA development. Methods: This prospective cohort study enrolled participants from the UK Biobank who had complete eGDR measurements and no pre-existing AAA at baseline (2006–2010). Participants were stratified into quartiles according to their eGDR values. The association between eGDR and AAA was assessed using Cox proportional hazards models with results expressed as the hazard ratio (HR) and 95% confidence interval (CI). Kaplan–Meier curves were generated to visualize cumulative AAA incidence across eGDR quartiles, whereas restricted cubic splines (RCSs) were applied to characterize the exposure–response relationship. Sensitivity and subgroup analyses were conducted to assess the robustness of the findings. Results: The final analytical cohort comprised 416,800 participants (median age: 58.0 years (IQR: 50.0–63.0), 45.83% male). During the median follow-up of 13.6 years, 1881 incident AAA cases were recorded. The Kaplan–Meier curve analysis demonstrated a higher cumulative AAA risk with decreasing eGDR quartiles (log-rank p < 0.05). The Multivariable Cox model confirmed that lower eGDR levels were significantly associated with increased AAA risk. When eGDR was assessed as categorical variable, compared with the participants in Quartile 1 group (reference group), the adjusted HR (95% CI) for those in the Quartile 2–Quartile 4 groups were 0.76 (0.66–0.87), 0.69 (0.59–0.80), and 0.46 (0.35–0.62), respectively. When eGDR was evaluated as a continuous variable, a 1-unit increment in eGDR corresponded to a 12% reduction in AAA risk (HR: 0.88, 95% CI: 0.85–0.90). After excluding patients with pre-existing diabetes or short-term follow-up, the sensitivity analysis produced similar results. A subgroup analysis further maintained the association between eGDR and AAA. Furthermore, the RCS curve revealed a nonlinear association between eGDR and AAA incidence risk (p for nonlinearity ≤ 0.05), identifying a threshold value of 7.78. Conclusions: Our study demonstrates that reduced eGDR levels are independently associated with elevated AAA risk, exhibiting a nonlinear dose–response relationship characterized by a threshold effect at 7.78. These findings position eGDR as a potentially valuable biomarker for AAA risk stratification and interventional strategies.